Strengthening the Principle of Prudence for Notaries in the Preparation of Digital-Based Deeds as an Effort to Renew Notarial Law - Jimmy Tanal; ⁠Effendy Lod Simanjutak (CV. Green Publisher Indonesia, 2026)
This study is purposed to analyze and formulate the strengthening of the notary's prudential principles in the creation of digital-based agreement deeds as part of the reform of notarial law in Indonesia. By examining Law Number 30 of 2004 concerning the Position of Notary as amended by Law Number 2 of 2014 concerning Amendments to the UUJN, the Civil Code, and Law Number 11 of 2008 concerning Information and Electronic Transactions in conjunction with Law Number 19 of 2016 concerning Amendments to the ITE Law, the research method used normative juridical with a statutory approach and a conceptual approach, along with relevant legal doctrines and literature. The results of the study indicate that the application of the notary's prudential principles in the creation of digital deeds still faces various problems, including inconsistencies in norms between the UUJN and the ITE Law, obstacles to online identity verification, the risk of data falsification, and the unclear legal status of digital deeds which have implications for the potential loss of the authentic nature of the deed. This situation has increased the risk of legal liability for notaries and disrupted legal certainty and protection for the parties. Therefore, legal reform is needed through regulatory harmonization, recognition of the cyber notary concept, and the development of technology-based standard operating procedures that include digital identity verification, the use of certified electronic signatures, and the recording of the deed-making process